Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1080/09540121.2012.720360
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of condom use and associated factors among Chinese female undergraduate students in Wuhan, China

Abstract: With the increasing prevalence of premarital sex among college students in China, our aim was to examine prevalence and determinants of condom use among sexually active female undergraduates at 16 university campuses in Wuhan. Questionnaires were distributed to 5076 unmarried female undergraduates, recruited using randomized cluster sampling by type of university and student major and grade, and anonymously completed questionnaires were received from 4769 (94% of enrollees). The complex samples logistic regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
0
13
2
Order By: Relevance
“…Previous studies have indicated that college students are at high risk of HIV/AIDS infections [6] , [7] . Meanwhile, some college students are engaging themselves in high levels of unprotected sexual intercourse with multiple sex partners and other risky sexual behaviors [8] , [9] . Thus, research and concerned organizations reach consensus to develop effective HIV preventive interventions among college students [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that college students are at high risk of HIV/AIDS infections [6] , [7] . Meanwhile, some college students are engaging themselves in high levels of unprotected sexual intercourse with multiple sex partners and other risky sexual behaviors [8] , [9] . Thus, research and concerned organizations reach consensus to develop effective HIV preventive interventions among college students [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Despite these challenges, a large number of college students (74–82%) in China have not had sexual intercourse (Tang et al. ; Xiao ; Zhou et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is greater than that of non-medical students of an Iranian university, called a great university of Mashhad (15.1%) [15], female undergraduates inWuhan (8.1%), China [5,18], and students of Dicle University (4.3%) in Turkey [19].This discrepancy could be explained by religious differences. In Iran and Turkey the dominant religion is Islam which does not only forbids premarital sex practice but also punishes the act.…”
Section: Discussionmentioning
confidence: 99%
“…In Iranthe rate of premarital sex is 15.1% among non-medical students of a great university of Mashhad, which was more common among males than females [15].In southern Iran (in Shiraz) the rate of premarital sex among the youth is 47.5% [16]. It is 63.9% among the unmarried youth of Vientiane Capital City, with higher prevalence among males than females [17].It is 8.1% among unmarried female undergraduates in China (Wuhan) [5,18].The rate of premarital sexual intercourse was low (4.3%) among students of Dicle University in Turkey, it being more prevalent among males than females (87.7% and 44.2% respectively) [19].The prevalence of premarital sexual practice in Africa seems to be higher compared to other continents. A very recent study conducted in Nigeria showed that the prevalence of premarital sex was 45.8% among nursing students, with more frequency among male students [20].…”
Section: Introductionmentioning
confidence: 99%